Alienation Theory and Its Relationship to Contemporary Arte Povera Practice - Conger, Elizabeth C (Auckland University of Technology, 2007)
In this Exegesis I explore the rehabilitation of marginalized materials through a sculptural practice. The materiality of the work focuses on the commonality of the everyday through selection editing and transparency of materials. The materiality and concern for material presence in my work are used metaphorically to explore ideas of alienation in contemporary sculpture. My work has been informed by the writing Berthold Brecht specifically his alienation effect [A-Effect], a theatrical and cinematic device "which prevents the audience from losing itself passively and completely in the character created by the actor, which consequently leads the audience to be a consciously critical observer". Through the use of situationist tactics in alienation works I seek to explore an atmosphere of fragile transience that can be recognized in ourselves even as we struggle against it.
Keywords: Trace; Alienation; Brecht; Haiku